Modeling of humidity stresses in a soil half-space - E. K. Agakhanov; C. A. Agakhanov; G. E. Agakhanov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. Solving the issues of reliability, durability and efficiency of buildings and structures is inextricably linked with the behavior of soils in their foundations. In order to establish a more realistic behavior of soils, the paper considers the determination of their stressstrain state, taking into account new factors, including physical influences, in particular, humidity.Method. Representing the structure of the soil in the form of a model composed of two elastic and one viscous elements, and assuming that the properties of the elastic elements do not change with changes in humidity, mathematical modeling of moisture stresses in the soil half-space was performed. The expediency of this model is explained by the fact that the transition to overly complicated material structure schemes introduces few significant corrections into the deformation laws and leads to serious calculation difficulties.Result. Replacing true time with conditional time leads to a significant simplification of the solution of the equation, since it reduces one part of it to a differential linear operator with constant coefficients. In this case, the opposite part can usually be considered as a given function of conditional time. The maximum value of stresses was obtained at full soil moisture, very low moisture intensity and very intensive moisture.Conclusion. By setting the appropriate moisture intensity, you can get the maximum stress that does not exceed the specified allowable value.